Neo-Classicism in Modern Arabic Poetry - Meraj Ahmad Meraj Al-Nadwi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
Modern neo-classical poetry constitutes a phase of literature that can be sharply separated from its immediate ancestry. Arab poets composed by imitative versifiers who very rarely employed it as a means of expressing fresh human experience. The bulk of late medieval Diwans (collections of verse) are replete with rhetorical devices and puns. Rather than addressing the major issues of life and society. Neo-classicism is the outcome of the revival of ancient learning through technological advancement. The purpose of the present study is to discuss the new school of thought named Neo- Classicism in modern Arabic Poetry. It also highlights its role of neo classicism to development of Modern Arabic poetry. يشكل الشعر الكلاسيكي الحديث مرحلة من تطور الأدب يمكن فصله بشكل حاد عن أصله المباشر. من الندرة نجد الشعراء العرب يستخدمونه كوسيلة للتعبير عن تجربة إنسانية جديدة. الجزء الأكبر من الدواوين في أواخر العصور الوسطى (مجموعات من الشعر) مليئة بالأدوات البلاغية والتورية. بدلا من معالجة القضايا الرئيسية للحياة والمجتمع. الكلاسيكية الجديدة هي نتيجة إحياء التعلم القديم من خلال التقدم التكنولوجي. الغرض من هذه الدراسة هو مناقشة المدرسة الفكرية الجديدة المسماة الكلاسيكية الجديدة في الشعر العربي الحديث. كما يسلط الضوء على دورها الكلاسيكي الجديد في تطوير الشعر العربي الحديث.